Orthopaedic nurses' engagement in clinical research; an exploration of ideas, facilitators and challenges. (November 2019) - Bench, Suzanne; Dowie-Baker, Julie-Anne; Fish, Paul
Abstract: Background: Previous international studies have identified individual and organisational barriers to nurses' research utilisation, but there is little data reporting on nurses' engagement in research design and/or delivery, particularly within the orthopaedic speciality. Aim: To explore orthopaedic nurses' views regarding the research priorities for neuro-musculoskeletal care and the perceived barriers and facilitators associated with their engagement in the research process. Methods: A single centre mixed methods study ( n = 75) employing a survey and 14 focus group discussions. Findings: The current sample of clinical orthopaedic nurses showed little evidence of research engagement. Research priorities focused on: 1) Understanding and improving patient and staff experiences; 2) Improving processes, systems and workload models; an 3) Interventions to improve clinical outcomes. Key themes arising from the focus group discussions were research activity, priorities and motivation, culture and leadership, and resources. Conclusion: These findings suggest that significant work is still required to build sufficient research capacity and capability within the nursing workforce. Key to success will be developing effective leaders who can create a positive and supportive research culture across an organisation to strengthen the research voice of nursing and which will drive improvements in future care.